Altered nuclei-specific thalamic functional connectivity patterns in multiple sclerosis and their associations with fatigue and cognition. (August 2019) - Lin, Fuchun; Zivadinov, Robert; Hagemeier, Jesper; Weinstock-Guttman, Bianca; Vaughn, Caila; Gandhi, Sirin; Jakimovski, Dejan; Hulst, Hanneke E; Benedict, Ralph HB; Bergsland, Niels; Fuchs, Tom; Dwyer, Michael G
Background: The thalamus, affected early in multiple sclerosis (MS), is a heterogeneous composition of functionally distinct nuclei and is associated with fatigue, cognition, and other outcomes. However, most previous functional imaging studies considered the thalamus only as a whole. Objective: To investigate MS-related abnormalities in nuclei-specific thalamic functional connectivity (FC) and their associations with fatigue and cognitive outcomes. Methods: Resting-state functional magnetic resonance imaging (fMRI) was analyzed in 64 MS patients and 26 healthy controls (HC). Whole-brain FC maps for four thalamic subregions seeds were computed for each subject. FC maps were compared between groups, and group by FC interaction effects were assessed for fatigue and cognitive measures. Results: MS patients had decreased FC between the left medial thalamic nuclei and left angular gyrus and reduced FC between the left posterior thalamic nuclei and left supramarginal gyrus, as well as decreased right medial thalamic nuclei connectivity with bilateral caudate/thalamus and left cerebellar areas ( p < 0.05 corrected). MS patients had increased FC between the left anterior thalamic nuclei and anterior cingulate cortex bilaterally. There were significant relationships between connectivity alterations and fatigue and cognitive measures between groups ( p < 0.05 corrected). Conclusion: FC alteration is nuclei-specific and is differentially associated with fatigue and cognition.